It's a small world : worldwide declining attendance and Disney theme parks - Gigliotti, Robert, (SAGE knowledge. Cases., 2016)
The global recession that began in 2008 affected the global theme park industry, and with it the theme park empire of The Walt Disney Company. This case examines the trends assessment and decision making required of Jay Rasulo, chair of Walt Disney Parks and Resorts, in response to these economic challenges.